Pyrolysis kinetics and multi-objective inverse modelling of cellulose at the microscale - richter,F; Rein,G (Fire Safety Journal, 2017)
The chemistry of pyrolysis, together with heat transfer, drives ignition and flame spread of biomass materials under many fire conditions, but it is poorly understood. Cellulose is the main component of biomass and is often taken as its surrogate. Its chemistry of pyrolysisis simpler and dominates the pyrolysis of biomass. Many reaction schemes with corresponding kinetic parameters can be found in the literature for the pyrolysis of cellulose, but their appropriatenessfor fire is unknown. This study investigated inverse modelling andthe blind prediction of six reaction schemes of different complexitiesfor isothermal and non-isothermal thermogravimetric experiments. We used multi-objective optimisation to simultaneously and separatelyinverse model the kinetic parameters of each reaction schemeto several experiments. Afterwards we tested these parameters with blind predictions. For the first time, we reveal a set of equally good solutions for the modelling of pyrolysis chemistry of different experiments. This set of solutions is called a Pareto front, and represents a trade-off between predictions of different experiments. It stems from the uncertainty in the experiments and in the modelling. Parameters derived from non-isothermal experiments compared well with the literature, and performed well in blind predictions of both isothermal and non-isothermal experiments. Complexity beyond the Broido-Shafizadeh scheme with seven parameters proved to beunnecessary to predict the mass loss of cellulose; hence, simplereaction schemes are most appropriate for macroscale fire models.Our results show that modellers should use simple reaction schemes to model pyrolysis in macroscale fire models.